Does Impedance Matter When Recording Spikes With Polytrodes? - Neto, Joana P.; Baião, Pedro; Lopes, Gonçalo; Frazão, João; Nogueira, Joana; Fortunato, Elvira; Barquinha, Pedro; Kampff, Adam R. (Frontiers in Neuroscience, 2018)
Extracellular microelectrodes have been widely used to measure brain activity, yet there are still basic questions about the requirements for a good extracellular microelectrode. One common source of confusion is how an electrode’s impedance affects the amplitude of extracellular spikes and background noise. Here we discuss how an electrode’s impedance affects data quality in extracellular recordings, which is crucial for both the detection of spikes and their assignment to the correct neurons. This study employs commercial polytrodes containing 32 electrodes (177 µm2) arranged in a dense array. This allowed us to directly compare, side-by-side, the same extracellular signals measured by modified low impedance (~100 kΩ) microelectrodes with unmodified high impedance (~1 MΩ) microelectrodes. We begin with an evaluation of existing protocols to lower the impedance of the electrodes. The poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate (PEDOT-PSS) electrodeposition protocol is a simple, stable, and reliable method for decreasing the impedance of a microelectrode up to tenfold. We next record in vivo using polytrodes that are modified in a ‘chess board’ pattern, such that the signal of one neuron is detected by multiple coated and non-coated electrodes. The performance of the coated and non-coated electrodes is then compared on measures of background noise and amplitude of the detected action potentials. If the proper recording system is used, then the impedance of a microelectrode within the range of standard polytrodes (~ 0.1 to 2 MΩ) does not significantly affect data quality and spike sorting. This study should encourage neuroscientists to stop worrying about one more unknown.